TOTAL PHENOLIC, TOTAL FLAVONOID CONTENTS AND ANTIOXIDANT ACTIVITY OF A FEW INDIGENOUS FRUITS GROWN IN MANIPUR - N. SWAPANA, TH. JOTINKUMAR; CH. BIJAYALAKSHMI DEVI; M. SUMARJIT SINGH; S. BROJENDRO SINGH; C. B. SINGH (The Bioscan, 2011)
Fruits are excellent sources of natural antioxidants, flavonoid and phenolic compounds. Methanolic extracts and petroleum ether extracts of 3(three) wild fruits have been measured by DPPH (1, 1-diphenyl, 2-picrylhydrazyl radical) method for antioxidant activity, Folin-Ciocalteu method for phenolic content and AlCl3 colorimetric assay for flavonoid contents respectively. The result indicates that high anti-oxidant, flavanoids and phenolic contents were observed in the methanolic extracts of the fruits as compared to the petroleum ether extracts. These results also confirmed that all the complex molecules like flavonols, polyphenols etc. are soluble in methanol as compared to petroleum ether.